Shelter-in-place as a strategy for mitigating exposure to toxic gas leaks in Malaysia: an in-depth analysis - Marzuki, Omar Faruqi; Abdul Gafor, Abdani; Adam, Nor Mariah; Lahuri, Azizul Hakim; Adam Assim, Mohd Ibrani Shahrimin; Yi, Ellie Lih Teo; Wan Ahmad, Wan Kamarudin (Islamic Azad University, 2024)
Malaysia's economic growth is significantly driven by its industrial sector, which includes high-risk industries prone to chemical accidents and toxic gas emissions. The shelter-in-place (SIP) strategy, which advises residents to stay indoors during chemical releases, has become a critical response measure. However, its effectiveness in Malaysia varies due to factors like building integrity, population density, chemical usage, and weather conditions that influence gas dispersion. This study assesses SIP's effectiveness in Malaysia by examining various contextual factors and highlighting the role of public awareness and preparedness. It uses case studies and best practices globally to propose improvements in building codes, construction practices, and public education to optimize SIP's effectiveness. This comprehensive analysis aims to enhance Malaysia's emergency response strategies, ensuring better community protection against chemical hazards. The study critically explores the strengths and limitations of SIP and provides recommendations for enhancing public safety protocols, thus contributing to the broader discourse on emergency preparedness in the face of industrial risks.